Partisipasi, Komunitarian, dan Eskatologi: Sebuah Imajinasi Konstruktif antara Membali Puang dan Theōsis - Christianto Sema Rappan Paledung (Asosiasi Teolog Indonesia, 2018)
This article proposes an imaginative constructive theology the membali puang in Rambu Solo' [Toraja funeral rites]. The soteriological notion of the Aluk Todolo [Way of the Ancestors] assumes that humans at first were divine beings and would eventually return [membali] to being divine, puang. I will situate membali puang in dialogue with the notion of theōsis from the tradition of Eastern Orthodoxy, as exemplified in the work of Vladimir Lossky. He argues that participation in Trinitarian life occurs only in the divine energy. Therefore, in an imaginative way, I propose that membali puang as theōsis enjoys a similar character of being participatory, communitarian, and eschatological.